2021
DOI: 10.1007/s40519-021-01201-9
|View full text |Cite
|
Sign up to set email alerts
|

Examining the validity and consistency of the Adult Eating Behaviour Questionnaire-Español (AEBQ-Esp) and its relationship to BMI in a Mexican population

Abstract: Purpose Appetitive traits in adults and their associations with weight can be measured using the Adult Eating Behaviour Questionnaire (AEBQ). The aim of this study was to confirm the factor structure of the Spanish AEBQ (AEBQ-Esp) in a Mexican sample and explore associations between the eight traits with body mass index (BMI). Method A sample of 1023 adults, mean age of 36.8 ± 12.8 years, was recruited from Guadalajara, Mexico. Researchers weighed and meas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

17
49
3
10

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 35 publications
(79 citation statements)
references
References 45 publications
17
49
3
10
Order By: Relevance
“…The results from this study showed no associations with either emotional over or undereating and BMI. These results differ with other publications that show that emotional overeating is positively associated with BMI in adult populations [12,15,30].…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…The results from this study showed no associations with either emotional over or undereating and BMI. These results differ with other publications that show that emotional overeating is positively associated with BMI in adult populations [12,15,30].…”
Section: Discussioncontrasting
confidence: 99%
“…Using the AEBQ-Esp, we measured the participants' emotional overeating and emotional undereating during the COVID-19 confinement. During the validation of the AEBQ tool in Mexicans prior to confinement, the mean of eating more through emotions was 2.54 (± 0.87) and eating less through emotions was 2.79 (SD: 0.88) [15]. The results from this study showed no associations with either emotional over or undereating and BMI.…”
Section: Discussioncontrasting
confidence: 55%
See 1 more Smart Citation
“…As described by Mallan et al, these differences may be attributed to the differences in sample characteristics. These similar findings were also found in other validation studies conducted in adolescents ( Hunot-Alexander et al, 2019 ) and Mexican adults ( Hunot-Alexander et al, 2021a ). Future studies require recruiting a diverse, gender balanced sample to continue to test the validity of the 7-factor versus the original 8-factor AEBQ among adult, especially as cultural differences may exist when describing relationships between eating behaviors and BMI ( He et al, 2021 ).…”
Section: Discussionsupporting
confidence: 90%
“…To date, AEBQ validation studies have been limited to five studies with adult samples (Australia, United States, Bulgaria, Mexico, and Canada) ( Mallan et al, 2017 ; Hristova, 2019 ; Zickgraf and Rigby, 2019 ; Hunot-Alexander et al, 2021a ; Jacob et al, 2021 ), one with younger adults, and three with adolescent samples (Chinese, United Kingdom, Polish) ( Hunot-Alexander et al, 2019 ; Guzek et al, 2020 ; He et al, 2021 ). To our knowledge, the AEBQ has not been validated in an English Canadian sample.…”
Section: Introductionmentioning
confidence: 99%